Các hợp chất glycolipit và phenolic từ cây mạ mân (Aganope balansae). - Toản, Trần Quốc; Thuần, Nguyễn Duy; Đạt, Nguyễn Tiến; Thảo, Nguyễn Phương; Hương, Hoàng Thanh; Minh, Châu Văn; Kiệm, Phan Văn (Vietnam Journal of Chemistry, 2012)
In our continuing study on the chemical constituents and biological activity of medicinal plants, a phytochemical investigation of the methanol extract of the roots from Aganope balansae led to the isolation of two glycosphingolipids, two glycerogalactolipids, two phenolic compounds together with a-sitosterol and daucosterol. By using spectroscopic methods including ESI-MS, 1D and 2D NMR, their structures were determined to be 1-O-b-D-glucopyranosyl-(2S,3S,4R)-2N-[(2'R)-2'-hydroxyoctadecananoyl]-14(E/Z)-docosene-1,3,4-triol (1), 1-O-b-D-glucopyranosyl-(2S,3S,4R)-2N-[(2'R)-2'-hydroxyoctadecananoyl]-14(E/Z)-tetracosene-1,3,4-triol (2), 1-O-(octadec-4-en-1-oyl)-3-O-[b-D-galactopyranosyl-(1®6)-b-D-galactopyranoside]-glycerol (3), 1-O-(octadec-4,6-diene-1-oyl)-3-O-[b-D-galactopyranosyl-(1®6)-b-D-galactopyranoside]-glycerol (4), 5,6-didehydrokawain (5), and 4-hydroxychalcone (6). Compounds 1-4 were newly identified and 5-6 were reported for the first time from this plant.